Interplay between family background and labour-market conditions in shaping students’ occupational status expectations - Hartung, Andreas [Verfasser]; Weßling, Katarina [Verfasser]; Steffen Hillmert [Verfasser] (My University, 2022)
“This study examines the relevance of labour-market conditions for individual occupational status expectations. We are particularly interested in students’ status expectations in the final stages of their school careers. Occupational expectations are an important basis for adolescents’ biographical decisions and corresponding transitions to vocational training and employment. By anticipating their likely labour-market situation, adolescents adjust their occupational choices; however, this anticipation is strongly moderated by their family background. We demonstrate this interaction using the example of school students in Germany’s secondary education’s tracked system. We link survey data from the German National Educational Panel Study to regionalised administrative data on unemployment. We find expectations for higher-status occupations in poor regional labour markets among students in non-academic school tracks. In contrast, students in the academic track aspire to lower status occupations in poor regional labour markets. In both cases, higher parental occupational status mitigates the impact of labour-market conditions on individual occupational status expectations. Our results indicate a greater awareness of structural conditions in the region among adolescents who are equipped with fewer familial resources.” (authors’ abstract; BIBB-Doku)
Keywords: P 2.1 Schulabgänger; G 1.3.2.2 Übergänge; G 1.3.2 Bildungsverhalten und -verläufe; G 1.2 Arbeitsmarkt; 370; 300; Schulabgänger; Berufseinmündung; Berufserwartung; Bildungsaspirationen; Arbeitsmarktsituation; Regionaler Arbeitsmarkt; Familie; Einflussfaktor